A new Prophaecasia species from Cambodia and the female characters of the genus (Lepidoptera: Tortricidae: Olethreutinae: Olethreutini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2017)
Prophaecasia lindae, n. sp., is described from Cambodia, along with notes on the female of the genus.